2001
DOI: 10.4049/jimmunol.166.12.7612
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of a Selective C1s Deficiency Associated with Early Onset Multiple Autoimmune Diseases

Abstract: We have investigated the molecular basis of selective and complete C1s deficiency in 2-year-old girl with complex autoimmune diseases including lupus-like syndrome, Hashimoto’s thyroiditis, and autoimmune hepatitis. This patient’s complement profile was characterized by the absence of CH50 activity, C1 functional activity <10%, and undetectable levels of C1s Ag associated with normal levels of C1r and C1q Ags. Exon-specific amplification of genomic DNA by PCR followed by direct sequence analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 22 publications
(20 reference statements)
1
29
1
Order By: Relevance
“…These conditions of the patients in this family appear to be different from those of previously reported cases (15)(16)(17)(18). It has been reported that a patient with a homozygous 4-bp deletion in exon X had SLE-like symptoms and chronic glomerulonephritis (15).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…These conditions of the patients in this family appear to be different from those of previously reported cases (15)(16)(17)(18). It has been reported that a patient with a homozygous 4-bp deletion in exon X had SLE-like symptoms and chronic glomerulonephritis (15).…”
Section: Discussioncontrasting
confidence: 51%
“…It has been reported that a patient with a homozygous 4-bp deletion in exon X had SLE-like symptoms and chronic glomerulonephritis (15). A patient with a homozygous Arg534X in exon XII had SLE-like symptoms, Hashimoto's thyroiditis, and autoimmune hepatitis (16). Thus the previous cases had in common immune complexrelated diseases or autoimmune diseases, especially SLE-like symptoms.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The most drastically altered gene was C1s , which is involved in complement system. In humans, C1s deficiency has been reported to associate with lupus nephritis [13,14,15,16,17]. Although it has not been fully understood what activity of the early proteins in the classical pathway of complement protects normal humans from development of lupus nephritis, clearance of immune complexes is thought to be a candidate activity [18].…”
Section: Discussionmentioning
confidence: 99%